Contribution of knowing in practice to dynamic capabilities. Issue 1 (14th January 2019) - Linden, Ane Isabel; Bitencourt, Claudia; Muller Neto, Hugo Fridolino
Abstract : Purpose: This paper aims to discuss the contribution of knowing in practice (KP) to the development of dynamic capabilities (DC) in the context of health-care organizations. Design/methodology/approach: The authors develop a case study in a Brazilian hospital in three stages using the data collection techniques of interviews, focus groups, shadowing and conjoint analysis. The participants were health-care employees, supervisors, project managers and members of the board of directors. Findings: This paper identifies the contribution of KP to develop DC based on strategic practices and their respective microprocesses as key elements to DC microfoundations. In the end, the paper points out a mutual contribution between the theoretical approaches. Research limitations/implications: This proposal makes sense in organizations where the practices have a strategic nature, such as hospitals and service providers. Practical implications: This study suggests an alignment between strategic and operational views, stimulating learning across organizational levels. Originality/value: KP helps to give DC a tangible form by including a human dimension into microfoundations, giving voice to practitioners in the strategic decisions. The integration of KP and DC approaches allows organizations to perceive DC in daily practices making DC present in every organizational level, stimulating a continuous organizational learning process.